Mesh use does not affect the outcome of elective open hernia repair in cirrhotic patients - Aksoy, Fuat; Buyukpolat, Burak; Balcin, Ozkan; Polatkan, Volkan; Kaya, Ekrem (Frontiers in Surgery, 2025)
PurposeThe aim of the study is to evaluate the outcomes of elective and emergency umbilical and inguinal hernia repairs in cirrhotic patients, focusing on the controversial use of mesh and its relationship with the Model for End-Stage Liver Disease (MELD) score.MethodsA retrospective analysis of patients with open surgical hernia repair on cirrhosis between January 2007 and December 2022 was performed. Patients were divided into 2 main groups: those with and without mesh. Demographic characteristics, perioperative factors, postoperative complications, recurrence, and first 90-day mortality rates were compared.ResultsSixty-two patients were included in the study. Mesh use was more common in inguinal hernia repairs, while mesh-free repairs were predominant in umbilical hernias. No significant difference was observed in postoperative complications between the groups, but comorbidities were more common in the mesh group. Ascites and emergency vs. elective status did not significantly affect the decision to use mesh. No significant difference was found between the two groups in terms of recurrence. A positive correlation was determined between higher MELD scores and 90-day mortality, regardless of mesh use. (p < 0.01).ConclusionsMesh can be safely used in hernia repairs in cirrhotic patients with appropriate perioperative management. However, it should be kept in mind that mortality may increase as the MELD score increases.